Islamic Economic Law and Sustainable Development: Bridging Ethics, Law, and Policy - Parviz Hasanov; Amin Songgirin; Ahmad Reza Hariyadi; Konul Madadzade (Journal of Islamic Law and Legal Studies, 2026)
This study explores the role of Islamic economic law in promoting sustainable development by establishing an integrated relationship between ethical values, legal frameworks, and public policy. Although sustainable development has emerged as a major global agenda, its implementation continues to face challenges due to the limitations of conventional economic and legal systems, which often prioritize efficiency and economic growth while overlooking ethical and social dimensions. Employing a qualitative research approach through content analysis, this study examines classical Islamic jurisprudence, contemporary scholarly literature, and relevant policy documents to analyze the alignment between Islamic economic principles and sustainability frameworks. The findings demonstrate that Islamic economic law provides a comprehensive and ethically oriented framework based on fundamental principles, including tawhid (unity), adl (justice), maslahah (public interest), and maqasid al-shariah (objectives of Islamic law). These principles are manifested through various institutional and legal instruments, such as zakat, waqf, and risk-sharing financial mechanisms, which contribute to social justice, economic inclusion, financial resilience, and environmental sustainability.